2015
DOI: 10.1097/inf.0000000000000698
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline Therapy for Late-Onset Sepsis in Preterm Infants

Abstract: Background:The role of pentoxifylline (PTX) in reducing mortality associated with neonatal sepsis is not well established. We aimed to assess the efficacy and safety of PTX as an adjunct to antibiotics on mortality and morbidity in preterm infants with late-onset sepsis (LOS). Methods: Double blind, randomized controlled trial was conducted on 120 preterm infants with LOS. They were randomly assigned to receive either intravenous PTX 5 mg/kg/hr for 6 hours on 6 successive days or placebo. Death before hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 31 publications
4
47
0
1
Order By: Relevance
“…Allerdings muss die Evidenz aufgrund der heterogenen Studienqualität als niedrig bezeichnet werden [131]. In einer anderen Studie [132] war die Mortalität und Kurzzeitmorbiditätunbeeinflusst,jedochsankenunterPentoxifyllin die Inzidenzen von DIC und Thrombozytopenie sowie die Gesamtdosis verabreichter Katecholamine im Vergleich zur Placebogruppe. Die in den Studien verwendete Dosierung betrug 5 mg/kg/h als Infusion über 6 h an 5-6 konsekutiven Tagen.…”
Section: Pentoxifyllinunclassified
“…Allerdings muss die Evidenz aufgrund der heterogenen Studienqualität als niedrig bezeichnet werden [131]. In einer anderen Studie [132] war die Mortalität und Kurzzeitmorbiditätunbeeinflusst,jedochsankenunterPentoxifyllin die Inzidenzen von DIC und Thrombozytopenie sowie die Gesamtdosis verabreichter Katecholamine im Vergleich zur Placebogruppe. Die in den Studien verwendete Dosierung betrug 5 mg/kg/h als Infusion über 6 h an 5-6 konsekutiven Tagen.…”
Section: Pentoxifyllinunclassified
“…In previous neonatal pilot studies, PTX improved endothelial cell function, reduced coagulopathy in sepsis and NEC and diminished intestinal permeability by reducing myeloperoxidase activity and oxygen free radical generation [4]. PTX also significantly reduces inflammatory host responses to various stimuli in neonatal blood in vitro and in vivo [5][6][7]. A recent Cochrane review concluded that PTX increases survival and shortens length of hospital stay in neonates with sepsis, and recommended appropriately powered clinical trials be undertaken to confirm these findings [8].…”
Section: Introductionmentioning
confidence: 95%
“…PTX competitively inhibits phosphodiesterases in a range of cells and tissues, thereby increasing intracellular cAMP, a second messenger which acts via protein kinase A to suppress gene transcription of proinflammatory mediators including tumor necrosis factor (TNF) (5,6). Due to its anti-TNF activity, PTX has been studied in animals and human adults and newborns to ameliorate inflammatory conditions such as sepsis, BPD, meconium aspiration, and hypoxic ischemic encephalopathy (7)(8)(9)(10)(11). Adverse reactions of PTX in adults include gastrointestinal and CNS symptoms, whereas significant adverse reactions at therapeutic doses are rare in adults (www.pdr.net/drug-summary/Pentoxifylline, www.fda.…”
mentioning
confidence: 99%